(Inter) cultural investigation: Kenya in German crime fiction (Journal for Studies in Humanities and Social Sciences, 2015)
Despite its marginalised appearance in politics and economics and being reduced to crime, chaos and catastrophes, the African continent has lately featured regularly in crime fiction (Picker 2011). African crime fiction, meaning crime fiction written by African authors, but also crime fiction set in Africa and written by non-Africans, is on a rise. Kenya has been among the popular crime settings in German crime fiction since the 1970s. A number of crime novels make use of a German investigator and an African setting and feature crosscultural as well as intercultural investigation teams. This paper presents Geert Hofstede’s cultural dimensions and analyses the German crime novels of Henry Kolarz, Detlef Wolff and the trilogy of the Swiss author Peter Höner, all set in Kenya. The paper investigates the portrayal of cultural encounters and multicultural cooperation and to what extend the novels show an intercultural investigation. Furthermore, it outlines similarities of novels in regard to the (inter)cultural set up.